2015
DOI: 10.1038/srep12696
|View full text |Cite
|
Sign up to set email alerts
|

The role of silicon in physiology of the medicinal plant (Lonicera japonica L.) under salt stress

Abstract: Silicon(Si) is the only element which can enhance the resistance to multiple stresses. However, the role of silicon in medicinal plants under salt stress is not yet understood. This experiment was conducted to study the effects of silicon addition on the growth, osmotic adjustments, photosynthetic characteristics, chloroplast ultrastructure and Chlorogenic acid (CGA) production of Honeysuckle plant (Lonicera japonica L.) under salt-stressed conditions. Salinity exerted an adverse effect on the plant fresh weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 36 publications
4
37
0
3
Order By: Relevance
“…For example, 85.73 mM NaCl increased the water saturation deficit in weak roots and limited the biomass accumulation of individual R. pseudoacacia [11]. The growth of the medicinal plant, L. japonica, was reduced by 200 mM NaCl because of negative effects on the ionic uptake and their distribution to plant organs [12]. Oxidative factors are prevalent in both lower and higher salinity conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, 85.73 mM NaCl increased the water saturation deficit in weak roots and limited the biomass accumulation of individual R. pseudoacacia [11]. The growth of the medicinal plant, L. japonica, was reduced by 200 mM NaCl because of negative effects on the ionic uptake and their distribution to plant organs [12]. Oxidative factors are prevalent in both lower and higher salinity conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the results of increasing total chlorophylls in salinity stressed plants due to nano silicon application are in harmony with those reported by Kalteh et al (2014). Other studies (Bayat et al 2013 ;Mateos-Naranjo et al 2013;Gengmao et al 2015 andEsmaeili et al 2015) reported that application of Si in bulk materials (potassium silicate) resulted in increasing total chlorophylls or K% in salinity stressed plants.…”
Section: Chemical Constituentsmentioning
confidence: 99%
“…Also, the slight increases (insignificant) in vegetative growth and flowering parameters of salt stressed plants due to nano silicon treatments are in agreement with those reported by Kalteh et al (2014) who found that nano silicon application increased leaves fresh and dry weights of basil salinity stressed plants. Furthermore, previous studies (Rahimi et al 2011;Bayat et al 2013 ;Mateos-Naranjo et al 2013;Gengmao et al 2015 andEsmaeili et al 2015) reported that application of Si in bulk materials (potassium silicate or sodium silicate) increased growth and flowering parameters of salt stressed ornamental plants.…”
Section: Interaction Between Effects Of Irrigation Water Salinity Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, chlorogenic acid is an important intermediate in lignin biosynthesis and was reported to be a chemical sensitizer responsible for human respiratory allergy against certain types of plant materials [24]. Review articles report modest blood pressure lowering effects from chlorogenic acid administration [25]. Interestingly, cinnamic acid is a precursor to the sweetener aspartame via enzyme-catalyzed amination to phenylalanine and its major use in the manufacturing of the methyl, ethyl, and benzyl esters for the perfume industry.…”
Section: Discussionmentioning
confidence: 99%